Development of a robust multi-objective model for green capacitated location-routing under crisis conditions with time value of money - Shima Roosta; Seyed Milad Mirnajafi Zadeh; Hamid Bazargan Harandi (تصمیم گیری و تحقیق در عملیات)
Purpose: Location-Routing Problem (LRP) is a strategic supply chain design problem aimed at meeting customer demands. LRPs involve selecting one or more depot sites from a set of potential locations and determining the best routes to connect them to demand points. With the rising awareness about the environmental impacts of transportation over the past years, using green logistics to mitigate these impacts has become increasingly important.Methodology: To compensative a gap in the literature, this paper presents a robust bi-objective Mixed-Integer Linear Programming (MILP) model for the Green Capacitated Location-Routing Problem (G-CLRP) with demand uncertainty and the possibility of failure in depots and routes.Findings: The final result of this robust multi-objective model is to set up the depots and select the routes that offer the highest reliability (maximizing network service) while imposing the lowest cost and environmental pollution. The paper also provides a numerical analysis and a sensitivity analysis of the solutions of the model.Originality/Value: Determining backup depots and increasing network serviceability for LRPs.